Construction of nested 4-dimensional complex lattices in order to realize interference alignment onto a lattice - Trinca, Cibele Cristina; Belfiore, Jean-Claude; De Carvalho, Edson D. [UNESP]; Filho, Jozué Vieira [UNESP] (My University, 2015)
Interference is usually viewed as an obstacle to communication in wireless networks, so we develop a new methodology to quantize the channel coefficients in order to realize interference alignment onto a 4-dimensional complex lattice and our channel model is the same as the compute-and-forward strategy. In this work, we furnish one example of channel quantization, which is related to the dimension 8 (real) or 4 (complex), and we make use of the binary cyclotomic field Q(?16), where ?16 is the 16-th root of unity.
Keywords: Binary Cyclotomic Field; Channel coding; Interference alignment; Lattice